Effect of Metabolic Syndrome and Individual Components on Colon Cancer Characteristics and Prognosis - Silva, Ana; Pereira, Sofia S.; Monteiro, Mariana P.; Araújo, António; Faria, Gil (Frontiers in Oncology, 2021)
Metabolic syndrome (MS) is recognized as a risk factor for colon cancer (CC). However, whether the cluster of metabolic changes that define MS also influence CC prognosis remains unclear. Thus, our aim was to investigate whether the presence of MS or any of the MS individual components could provide prognostic information on tumor phenotype and survival outcomes. Clinical and pathological data from patients with CC (n=300) who underwent surgical resection at a single tertiary hospital were retrospectively collected to evaluate presence of MS components and diagnostic criteria, CC phenotype and disease outcomes. Patients were allocated into two groups according to the presence or absence of MS (n= 85 MS vs n= 83 non-MS). The overall prevalence of MS individual components was 82.7% for increased waist-circumference (WC), 61.3% for high blood pressure (BP), 48.8% for low HDL-cholesterol, 39.9% for high fasting glucose, and 33.9% for hypertriglyceridemia. Patients in the MS group presented smaller tumors (p=0.006) with lower T-stage (p=0.002). High BP (p=0.029) and hypertriglyceridemia (p=0.044) were associated with a smaller tumor size, while low-HDL (p=0.008) was associated with lower T-stage. After propensity score matching using age, tumor size and staging as covariates high-BP (p=0.020) and WC (p=0.003) were found to influence disease-free survival, but not overall survival. In conclusion, despite MS being an established risk factor for CC, our data does not support the hypothesis that MS components have a negative impact on disease extension or prognosis. Nevertheless, a protective role of BP and lipid lowering drugs cannot be excluded.